(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Sound field behaviour in an acoustic enclosure is an important part of the cabin passenger transport vehicle design, concert halls, conference rooms, etc., different analytical methods are available to design engineers, which has its strengths and weaknesses. Cavities in a low-frequency band and negligible absorption on the walls can be modelled by Modal Analysis and Finite Element Method. However, when the frequency band increases, both methods become computationally expensive and Statistical Energy Analysis or Sabine model can be an efficient approach. These methods assume deterministic treatment and almost nothing is known about the effect of uncertainties in the parameters, acoustic velocity and acoustic pressure inside cavities. This paper presents a study on the patterns of density and energy flow generated guide acoustic waves at high frequencies including uncertainties in geometric parameters and property of fluids. The waveguide is modelled by the Spectral Element Method Energy. The mean and variance of energy density and the flow of energy are calculated by using Monte Carlo simulation. Numerical examples show the influence of the random parameters in the different variation of the waveguide.